2010
DOI: 10.4314/tjpr.v9i1.52030
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Quinine and Artemether in the Treatment of Severe Malaria in Nigerian Children

Abstract: Purpose: Nigeria has adopted quinine as the drug of first choice in the treatment of severe malaria and artemether as an alternative therapy. (p = 0.829, OR = 0.883, 95 %CI = 0.284 to 2.742). Conclusion: Artemether is a comparable alternative to quinine in the treatment of severe paediatric malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…This study found that most of the patients were married female, below the age of 50 years and engaged in low to moderate levels of physical activity. Similar sociodemographic characteristics was observed in previous studies conducted in Nigeria (Enwere et al, 2006;Adibe et al, 2009;Jimoh et al, 2011;Eze et al, 2011;Dada et al, 2021). This may be related to the fact that the health seeking behaviour of most urban dwellers in the country is relatively comparable and more female visit the public hospital compared to the male counterparts (Adams & Carter, 2011).…”
Section: Medication Prescriptionsupporting
confidence: 88%
“…This study found that most of the patients were married female, below the age of 50 years and engaged in low to moderate levels of physical activity. Similar sociodemographic characteristics was observed in previous studies conducted in Nigeria (Enwere et al, 2006;Adibe et al, 2009;Jimoh et al, 2011;Eze et al, 2011;Dada et al, 2021). This may be related to the fact that the health seeking behaviour of most urban dwellers in the country is relatively comparable and more female visit the public hospital compared to the male counterparts (Adams & Carter, 2011).…”
Section: Medication Prescriptionsupporting
confidence: 88%